How does the COVID-19 outbreak affect the causality between gold and the stock market? New evidence from the extreme Granger causality test. (September 2022) - Hong, Yanran; Ma, Feng; Wang, Lu; Liang, Chao
Abstract: The causal relationship between gold and stocks has been widely studied, while their causality and the long- and short-run characteristic of this relationship have not been examined under different shocks. The purpose of this paper is to fill this gap. Meanwhile, considering the impact of the COVID-19 outbreak on gold and stock markets, we also aim to investigate whether the relationship changes after this epidemic. With invoking the time- and frequency-domain extreme Granger causality tests, we find that a significant causality between gold and stock usually comes from extreme shocks, displaying as the long-term causality running from gold shocks to stock shocks while the fickle impact of stock shocks on gold shocks. Besides, empirical results suggest that the causality between gold and stock shocks is greatly promoted after this epidemic. The present study is useful for investors and policymakers, as it has reference significance when dealing with subsequent extreme shocks or events. Highlights: This paper examines the extreme causality between gold and stock markets from the perspective of time and frequency domain before and after the COVID-19 outbreak. The causal relationship between gold and the stock market is usually driven by extreme shocks. The extreme causality between gold and the stock markets is largely influenced by the COVID-19 havoc. The medium- and long-term relationships are more apparent than the short-term linkage, whether before or after the COVID-19 pandemic.